LITERATURE OF REVIEW THE INFLUENCE OF EMPLOYEE JOB SATISFACTION ON EMPLOYEE COMPENSATION AND JOB CHARACTERISTICS (Production Department of PT. Arcelindo Lestari) - Azril Hikmal Arsya (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This research examines the literature review of theinfluence of employee job satisfaction on employeecompensation and job characteristics. This researchwas conducted at PT Arcelindo Lestari which focusedon the production department. This research willfocus on discussing the influence of 2 independentvariables and 1 dependent variable. This researchuses a quantitative approach using a questionnaire asa medium for conveying information. This researchuses SPSS 28 for Windows as a tool for analyzingresearch data